Pancreaticoduodenectomy for periampullary tumors at Dr. Cipto Mangunkusumo Hospital, Jakarta (Faculty of Medicine Universitas Indonesia, 2004)
We reported our experience on 31 pancreaticoduodenectomy out of 141 periampullary tumors during 1994 until 2002; 16 of them were female, and age average 17-68 years. Jaundice was the most common presenting sign; 14 patients showed plasma albumin lower than 3.5 g/dl, and 10 patients had bilirubin level more than 10 mg/dl. We performed classical Whipple technique in 17, pyloric preserving pancreaticoduodenectomy in 11, and total pancreaticoduodenectomy in 3 patients. The mean of operative time was 436 minutes (290-570 minutes). The patients were grouped into 2 periods, between 1994-1999 and thereafter. With experience, the amount of blood loss has decreased from 2000 ml to 400 ml. Histopathologic results showed adenocarcinoma of the pancreas head in 11, adenocarcinoma of the ampulla of Vater in 11, carcinoma of duodenum in 4, head of pancreas benign cyst in 2, and benign tumor in 3 patients. The surgical mortality was 4 in the first 12 patients, in contrast to only 1 in the last 19 patients. The most serious complication was pancreatic leakage in 14 patients, in 4 of them it was responsible as the cause of death. The length of stay after operation varied between 12 and 47 days. Until the end of this report 7 patients are still alive, and 4 patients lost of contact. Recurrence was detected in 13 out of 22 survivors, occurring between 4 to 24 months after operation and 12 patients died 2-3 months later. Three patients died due to other causes. We conclude that pancreoticoduodenectomy is an effective technique, and the operative mortality is decreasing. Furthermore, morbidity especially from pancreatic leakages can be treated in our hospital. (Med J Indones 2004; 13: 166-70) Keywords: operative outcome, Whipple technique, pancreatic leakage